Advances in Enterprise Engineering XI : 7th Enterprise Engineering Working Conference, EEWC 2017, Antwerp, Belgium, May 8-12, 2017, Proceedings /: 7th Enterprise Engineering Working Conference, EEWC 2017, Antwerp, Belgium, May 8-12, 2017, Proceedings. (2017) - Unknown
No abstract available